The Effect of Aerobic Exercise on Pregnancy Outcomes - N Motahhari Tabari, (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Exercise during pregnancy is interested for pregnant women, because of the positive effects on cardiovascular status, decrease of risk of obesity and low back pain, but there is worry about fetal outcomes. Since there are controversies in various studies about this effect, making a conclusion is difficult. The purpose of this study was to assess the effect of a planned aerobic exercise program on the pregnancy outcomes.METHODS: This study was a randomized clinical performed on 44 pregnant woman with 24 to 32 weeks gestational age were divided in case (n=20) and control group (n=24). Two groups were matched for mother age, BMI, Para, gestational age and socioeconomic status. Included criteria were single pregnancy with intact fetal membrane and excluded criteria were contraindications of exercise in pregnancy. Exercise program training includes stretching and flexibility exercise for 15 minutes and then aerobic exercise includes constant walking for 5 to 15 minutes. Pregnancy outcomes were assessed included: delivery mood, cause of cesarean section, increase of mother and fetus weight and duration of pregnancy and compared in two groups.FINDINGS: The increase of mother weight was lower in case group after two months (4.34kg VS 5kg), but the difference was not significant. The mood of delivery was not significantly different between two groups, although the rate of cesarean section and cesarean section for prolonged labor was higher in control group. There was no case of preterm or postterm delivery. No significant difference was seen between two groups about duration of pregnancy. After two months the increase of fetal weight was higher in case group (426.25gr VS 369.05gr) but showed no significant difference. Partial difference of increase in fetal weight was not significant between two groups during study.CONCLUSION: The results of this study showed that not only doing or continue the exercise has no negative effect on mother and fetus but also it has positive effect on pregnancy outcomes.